Typical bronchial carcinoid with local metastasis and coexisting tuberculosis in the same lung: A case report - Shalini Mullick (The Journal of Association of Chest Physicians, 2014)
Bronchial carcinoids comprise of <3% of lung tumours. Though typical carcinoids are usually benign, they may, uncommonly, metastasise to regional lymph nodes as well as to distant sites, and a few cases have been associated with active tuberculosis. We report an unusual case of a typical bronchial carcinoid with regional metastasis and tuberculosis. The metastatic deposits were present in small lymph nodes, emphasizing the need for careful sampling, while grossing. In addition, coexisting tuberculosis in the same lung of the patient make the case an extremely rare one.